Syrian voices: an exploration of the language learning needs and integration supports for adult Syrian refugees in Ireland. Issue 1 (2nd January 2021) - Ćatibušić, Bronagh; Gallagher, Fiona; Karazi, Shadi
ABSTRACT: This paper describes a research project investigating language and intercultural support for adult Syrian refugees in Ireland under the Irish Refugee Protection Programme (IRPP). Learning the language of the host community has been identified as a crucial factor in resettlement satisfaction for adult refugees, with particular difficulties reported in relation to older refugees, women, and those with low levels of literacy. This paper focuses on the voices of twenty-six adult Syrian refugees concerning their ongoing acquisition of English and interactions with members of the local community in the one to two years since their arrival, exploring their views regarding the importance of learning English and their perceptions of what constitutes both useful language learning supports and particular challenges for them. Findings point to the importance of language acquisition for adult refugees not only in relation to their prospects for employment, social interaction, and access to accurate information but also in relation to their sense of personal well-being, dignity and autonomy. The research highlights the need for a flexible approach to language learning and teaching in this context, utilising a range of technological and bilingual supports, which respond to the particular circumstances, complex needs and previous learning experiences of the learners.